Bioactive potential of catechin producing endophytic fungi from Camellia sinensis L. - Goyal, Riya (My University, 2024)
Medicinal plants are used from past times to treat various diseases as it has lot of remedial properties. Novel bioactive compounds isolated from endophytic fungi has lot of medicinal values due to which scientists show great interest to explore the endophytic fungi. The aim of current research work is to isolate endophytic fungi from Camellia sinensis, screening of extracts for their bioactivities like antioxidant and anti-microbial properties and for presence of EGCG and catechin. Bioactivity tests were performed on crude extracts for further screening of the isolates. PP42(a) showed maximum reducing power (78.32%) of ferric ions (Fe3+) to ferrous ions (Fe2+) and IC50 value was 100μg/ml followed by PP36(a) (73.56%) and then by PP16(a) (73.47%) at 1000μg/ml. PP43(a) showed maximum scavenging activity (72.28%) to scavenge the superoxide radical ions followed by PP36(a) (72.20%) and then by PP42(a) (72.89%) at 1000μg/ml. Among the four selected screened extracts, PP36(a) showed maximum (72.99%) radical scavenging activity at 800μg/ml and IC50 value was 200μg/ml by superoxide anion scavenging assay. PP5B(a) showed maximum scavenging activity (74.57%) to scavenge the free radical ions followed by PP45(a) (71.68%) and then by PP16(a) (71.43%) at 1000μg/ml. Among the four selected screened extracts, PP5B(a) showed maximum (52.82%) free radical scavenging activity at 400μg/ml and IC50 value was 400μg/ml by DPPH assay. PP5B(a) showed maximum (74.74%) inhibition of neurotransmission followed by PP36(a) (74.18%) and then by PP16(a) (72.67%) at 1000μg/ml. PP5B(a) showed maximum (65.29%) inhibition of neurotransmission at 400μg/ml and IC50 value was 200μg/ml by AChE assay. PP16(a) showed maximum (34.5mg) polyphenol content followed by PP42(a) (34.09 mg). PP36(a) showed maximum (8.7 mg) flavonoid content followed by PP16(a) (8.28 mg). PP16(a) shows two bands F2 and F4. PP42(a) showed two bands F3 and F4 and a very light band of catechin is also observed. PP36(a) showed two bands F2 and F4. PP5B(a) showed maximum bands F1, F2, F3 and F4. Among the four isolates, none of them contain EGCG whereas 3 of them have a prominent catechin band. Crude extracts were tested against three bacterial cultures Pseudomonas aeruginosa, Staphylococcus aureus, E. coli and one fungal cultures Candida albicans. PP42(a) and PP36(a) showed zone of inhibition against E. coli. So, from the above results it was cleared that endophytes have a considerable effect in pharma industry due to which there is strong need to explore the endophytic fungi fully.
Keywords: Endophytes; Camellia sinensis; catechins; antimicrobial activity